Viscothermal Behavior and Structural Characterization of Temperate Highland Himalayan Rice Cultivars. (28th December 2020) - Naseer, Bazila; Naik, Haroon Rashid; Hussain, Syed Zameer; Qadri, Tahiya; Beigh, Mushtaq Ahmad
Abstract: Four of five Indica and three japonica rice cultivars, widely cultivated under temperate condition in highland Himalayas are evaluated for nutritional, pasting and thermal properties and are subsequently subjected to structural characterization. Out of the different cultivars, highest peak viscosity (3990 cP), breakdown viscosity (2015 cP), final viscosity (5580 cP), setback viscosity (3605 cP); onset temperature (75.97 °C), peak temperature (83.17 °C), conclusion temperature (93.66 °C), enthalpy of gelatinization (6.66 J g −1 ) and peak height index (0.92) are recorded for Jhelum. Scanning electron microscopy (SEM) also reveals that some morphological difference existed in these genotypes. All the cultivars show an A type X‐ray diffraction pattern with different degrees of crystallinity ranging from 21.21 % to 39.42 %. ATR‐FTIR in combination with Raman spectroscopy provides some useful information about functional groups of molecules and validates that some dissimilarities exist in structure and chemical profile of these varieties. Based on the pasting behavior, Jhelum is considered best for cooking purposes while Koshikari, due to its good nutritional profile, can be explored for nutritional improvement programs in future. The outcome of this study serves as basic guideline to plan future research on such varieties and to formulate selection indices for developing quality rice from highland Himalayan rice cultivars. Abstract : The attenuated total reflection‐Fourier transform infrared spectroscopy spectra results reveal that the peaks in all the rice cultivars are within the range of 829.33 to 3831.70 cm −1 except Chenab. Based on the pasting behavior, Jhelum is considered best for cooking purposes while Koshikari due to its good nutritional profile can be explored for nutritional improvement programs in future.